2014
DOI: 10.4236/fns.2014.518191
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Fermentation Patterns, Diarrhea Incidence, and Performance in Weaned Piglets Fed a Low Protein Diet Supplemented with Probiotics

Abstract: To evaluate the effects of dietary protein levels and probiotic supplementation on microbial intestinal fermentation, diarrhea incidence, and performance in weaned piglets, 162 piglets were randomly assigned to three treatments: high-protein diet (20%), with antibiotics (HPa); high-protein diet (20%), without antibiotics (HP); and low-protein diet, without antibiotics but with probiotics (LPpb). Piglets and feed were weighed weekly to calculate the average daily gain (ADG), average daily feed intake (ADFI), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…toxic metabolites in the intestinal lumen, indicated by an increase in villi height and a better villi/ crypt ratio in non-ruminant animals (GARCÍA et al, 2014;SANTANA et al, 2012;NÖRNBERG, 2003), as seen with COS in piglets (HAN et al, 2007). In this study, the jejunum, which has excellent absorptive activity, demonstrated a direct correlation between villi height increasing levels of COS, corroborating the previous results of Liu et al (2008) indicating that 200 ppm COS had a positive effect on this characteristic.…”
Section: Crypt (µMsupporting
confidence: 80%
See 1 more Smart Citation
“…toxic metabolites in the intestinal lumen, indicated by an increase in villi height and a better villi/ crypt ratio in non-ruminant animals (GARCÍA et al, 2014;SANTANA et al, 2012;NÖRNBERG, 2003), as seen with COS in piglets (HAN et al, 2007). In this study, the jejunum, which has excellent absorptive activity, demonstrated a direct correlation between villi height increasing levels of COS, corroborating the previous results of Liu et al (2008) indicating that 200 ppm COS had a positive effect on this characteristic.…”
Section: Crypt (µMsupporting
confidence: 80%
“…The effects of these acids on the intestinal epithelia are related to an increase in cellular proliferation and activity, leading to an increase in the relative weight of this organ (ROBERFROID, 2002 For the relative weight of organs and the small intestine length (Table 5), a linear increase was observed for the relative weight of the large intestine and the dose of COS used. The use of Oliveira, E. R. et al with antibiotics, promotes an increase in large intestine relative weight, related to benefits in performance and intestinal health (GARCÍA et al, 2014). Moreover, this increases the total number of bacteria in this organ and reduces the total amount of E. coli and Clostridium spp.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, an increase in ammonia concentration has a detrimental effect on the health of the GIT and a negative effect on the growth and differentiation of intestinal epithelial cells [49,50]. Additionally, BCFAs and ammonia are toxic metabolites for the intestinal mucosa and most likely trigger PWND and the poor performance in piglets [39,51,52]. More importantly, the upregulated expression of ammonia may induce a disorder of the intestinal microbial balance during weaning [20].…”
Section: E Effect Of Dietary Protein On the Incidence Of Pwndmentioning
confidence: 99%
“…Lactic acid bacteria is most commonly used probiotic in livestock, and predominant at the early stage of pig gut microflora construction [36]. Increased lactic acid bacteria can reduce fecal pH and ammonia nitrogen levels [34,37], as well as prevent colonization of pathogenic organism colonization, therefore improve the natural microbiome and gut health [31]. Lots of bioactive antimicrobial chemical forms, including phenolic acids, quinones, flavonoids, tannins and alkaloids, have been identified and been used in animal nutrition [7,8].…”
Section: Discussionmentioning
confidence: 99%